PSI-23 Evaluating the temporal development of the rumen microbiota from birth to post-weaning. (7th December 2018) - O Hara, E; Kenny, D; McGovern, E; McCabe, M; Guan, L; Waters, S
Abstract: The resilience of the adult rumen microbiota to persistent manipulation has led to much interest in imprinting a favourable microbial pattern in the rumen during the early life developmental period. However, there is still a lack of knowledge on the extent to which several factors may influence rumen microbial establishment in early life. The objectives of this study were to characterise the development of the rumen microbial community from birth to post-weaning, and to assess the effects of environment and gender on these changes. Aberdeen Angus heifers (n=72) located on two separate research farms were artificially inseminated with semen from a single Aberdeen Angus bull, yielding 45 viable pregnancies. Calves were removed from their dam 48h post-partum, penned individually, and randomly assigned to one of 5 treatment groups; D7 (slaughtered at 7 days of age, n=8), D14(n=9), D21(n=9), D28(n=9), D96(n=10). Following euthanasia, the gastrointestinal tract was quickly exteriorised, and samples of solid- and liquid-associated digesta and tissue were collected from the rumen. 16S rRNA amplicon sequencing was used to assess microbial composition. PERMANOVA analysis of the OTU-level dissimilarity matrix showed significant effects of age, location, and sex on rumen microbial structure, with significant interactions between each (P<0.05). In particular, environment appeared to play a significant role in shaping the rumen microbial community, and this persisted to post-weaning. Bacterial composition changed significantly in the first month, and again post-weaning, consistent with calf growth and dietary change (P<0.05). Diversity was stable in early life, but significantly higher in post-weaned calves (P<0.05). We conclude that in early life, several factors including age, environment, and gender may contribute to patterns of microbial colonisation of the developing rumen.